2013
DOI: 10.14214/sf.893
|View full text |Cite
|
Sign up to set email alerts
|

Soil preparation method affects outplanting success of Norway spruce container seedlings on till soils susceptible to frost heave

Abstract: Soil preparation method affects outplanting success of Norway spruce container seedlings on till soils susceptible to frost heave Heiskanen J., Saksa T., Luoranen J. (2013). Soil preparation method affects outplanting success of Norway spruce container seedlings on till soils susceptible to frost heave. Silva Fennica vol. 47 no. 1 article id 893. 17 p. AbstractSoil preparation is a common practice that precedes outplanting of Norway spruce (Picea abies (L.) Karst.) in Finland as it enhances the survival and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…Frost heave primarily affects areas on drained peat soils in Latvia (Mangalis, 2004). Study in central Finland found that it has been present mainly on areas with ditch mounded and inverted soil (Heiskanen et al, 2013). Similar to our results, superior height growth of trees planted on mounds had been found also in numerous studies in Sweden and Finland (Saarinen, 2007;Lehtosalo et al, 2010;Uotila et al, 2010;Hallsby & Örlander, 2013).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Frost heave primarily affects areas on drained peat soils in Latvia (Mangalis, 2004). Study in central Finland found that it has been present mainly on areas with ditch mounded and inverted soil (Heiskanen et al, 2013). Similar to our results, superior height growth of trees planted on mounds had been found also in numerous studies in Sweden and Finland (Saarinen, 2007;Lehtosalo et al, 2010;Uotila et al, 2010;Hallsby & Örlander, 2013).…”
Section: Resultssupporting
confidence: 91%
“…These fi ndings are in line with our results where largest height differences were found between spruces growing on mounds and on unprepared soil (Figure 3). Lack of soil scarifi cation leads to much more frequent pine weevil damages even if the plants are treated by insecticide in the nursery (Heiskanen et al, 2013). For example, study in Finland had found 76% of Norway spruce seedlings gnawed in unscarifi ed spots during fi rst growing season in fi eld in contrast to only 1% gnawed on mounded spots (Heiskanen & Viiri, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations